SHELTER DOG TEMPERAMENT AND ITS INFLUENCE ON LEARNING OF BASIC COMMANDS AND ADOPTION RATE - Gurgel Galeb, Luciana do Amaral; Henrique Weber, Saulo; Duarte Borges, Tâmara; Welker Biondo, Alexander; Amanda Anater, Amanda; Graduanda Aline , Rodrigues Pianaro; Luiz de Sousa, Eros; Turra Pimpão, Cláudia (Revista Inclusiones, 2022)
This article's objective was to verify the influence of rescued dogs’ temperament on basic commands learning and adoption rates. Thus, 30 dogs were evaluated. Temperament data was collected employing the focal animal sampling method in three different environments. A 7-item selection of training commands was also applied in both basic obedience and retrieval tasks to improve dogs’ overall individual performance over time. The principal component analysis followed by Spearman’s correlation coefficient was used to analyze dog temperament scores for the adoption rate and the time dogs took to learn each training command. Lay down was positively correlated with stay (r=0.4, p<0.02), paw give (r=0.5, p<0.002) and crawl (r=0.4, p<0.009). Adoption rate was negatively correlated with lay down (r=-0.54, p<0.02), stay (r=-0.8, p<0.03) and crawl (r=-0.8 p<0.05). The time dogs took to learn specifics training commands was an important indicator that reflects their temperament and influences the adoption rate.